Polymorphism of immunoglobulin enhancer element HS1, 2A: allele *2 associates with systemic sclerosis. Comparison with HLA-DR and DQ allele frequency. Issue 9 (28th March 2007) - Frezza, D; Giambra, V; Tolusso, B; De Santis, M; Bosello, S; Vettori, S; Triolo, G; Valentini, G; Ferraccioli, G
Abstract : Objective: To investigate the relationship of the polymorphic enhancer HS1, 2 central to the 3′ enhancer complex regulatory region (IgH3′EC) of the immunoglobulin heavy chain genes with systemic sclerosis (SSc) disease and compare it with HLA-DR and DQ associations. Methods: A total of 116 patients with SSc were classified as diffuse (dSSc) or limited (lSSc), and as carriers of antitopoisomerase I (anti-Scl70) or anticentromere (ACA) antibodies. Allele and genotype frequencies were assessed in the population as a whole and in the two major subsets, dSSc and lSSc. The concentration of peripheral blood immunoglobulin levels was also determined and analysed according to the genotypes. Results: The analysis of genotypes for the four alleles of the HS1, 2A enhancer showed an increased frequency of allele *2 in the SSc cohort highly significant versus controls (57% vs. 40%, p<0.0001). Considering the autoantibody pattern, we found that the frequency of the 2/2 genotype was increased in ACA+ patients (42%) and anti-Scl70+ patients (31%) compared with the control group (15%). The differences of allelic frequencies among dSSc versus lSSc or ACA+ versus anti-Scl70+ patients were not significant, although highly significant when comparing each subgroup with the control group. HLA-DRB1*11 and DQB1*03 associated with SSc. No association was seen between HS1, 2A enhancer polymorphism and HLA alleles. Conclusions: These data confirm there was an increased risk of having SSc in carriers of allele *2, suggesting an intriguing function of this polymorphism for B-cell regulation.